Effects of exogenous insulin supplementation on lipid metabolism in peripartum obese dairy cows - Guo, Yuanyin; Zhao, Yihan; Wei, Ziang; Cao, Jie (Frontiers in Veterinary Science, 2025)
Cows with high body condition scores experience more severe negative energy balance (NEB) and undergo mobilization of more body fat during the peripartum period, leading to more production of nonesterified fatty acids (NEFA) and β-hydroxybutyric acid (BHBA). Postpartum insulin secretion is lower, and insulin resistance is stronger in obese cows. Exogenous insulin supplementation has been hypothesized as a key approach for regulating NEFA in these cows. In this study, we assessed the effects of exogenous insulin supplementation on lipid metabolism, key genes regulated by insulin, and the underlying regulatory mechanism. We selected 181 periparturient multiparous obese dairy cows for the study. Cows in the insulin group (n = 96) received subcutaneous injections of 200 IU insulin (5 mL) on postpartum days 1 and 7, while cows in the control group (n = 85) received subcutaneous injections of 5 mL physiological saline on the same days. The incidence of ketosis was recorded and compared between the two groups. The results demonstrated that postpartum insulin injections significantly reduced the incidence of type II ketosis and delayed the onset time. Meanwhile, a cohort experiment was conducted on 20 cows selected from 181 field trial cows, with 10 cows in the insulin group and 10 cows in the control group. Blood samples were collected for biochemical indicators and subcutaneous adipose tissue was collected for paraffin-embedding and sectioning and RNA sequencing analysis. The results showed that insulin supplementation postpartum reduced concentrations of NEFA and BHBA as well as BCS loss, but did not affect glucose. Additionally, the expression of SREBF1 in insulin signaling pathway and the downstream-regulated lipogenesis network genes were successfully upregulated in insulin-treated healthy group. High expression of SREBF1 may be a key for postpartum insulin supplementation to improve insulin resistance, significantly reduce NEFA concentrations, and prevent or treat ketosis and fatty liver in obese cows. Postpartum administration of insulin could effectively decrease alterations of adipocytes size, which also fully validates that postpartum insulin supplementation promotes lipogenesis and reduces NEFA release.